2006
DOI: 10.1086/508996
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Preterm Delivery and Neonatal Mortality after the Introduction of Antenatal Cotrimoxazole Prophylaxis among HIV‐Infected Women with Low CD4 Cell Counts

Abstract: Among 255 women with CD4 cell counts <200 cells/ micro L, the percentage of preterm births (< or =34 weeks of gestation) was lower (odds ratio [OR], 0.49 [95% confidence interval {CI}, 0.24-0.98]) after cotrimoxazole prophylaxis was introduced than before; there was a significant decrease in neonatal mortality (9% to 0%; P=.01) and a trend toward increased birth weight ( beta =114 g [95% CI, -42 to 271 g]). In contrast, there were no significant changes in these parameters over the same time interval among wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 38 publications
3
30
0
1
Order By: Relevance
“…Discrepancies between studies may be linked to patient and practice heterogeneity, as HIV disease stage, HIV-1 RNA load, and CD4 count are all potential confounders of timing of ART initiation in pregnancy and adverse pregnancy outcomes. For instance, women with advanced HIV infection are more likely to deliver prematurely and to receive ART early during pregnancy (38). In the current study, there were six (32%) preterm deliveries, which is consistent with other reports (23,36).…”
Section: Discussionsupporting
confidence: 92%
“…Discrepancies between studies may be linked to patient and practice heterogeneity, as HIV disease stage, HIV-1 RNA load, and CD4 count are all potential confounders of timing of ART initiation in pregnancy and adverse pregnancy outcomes. For instance, women with advanced HIV infection are more likely to deliver prematurely and to receive ART early during pregnancy (38). In the current study, there were six (32%) preterm deliveries, which is consistent with other reports (23,36).…”
Section: Discussionsupporting
confidence: 92%
“…3,2241 One paper reported the results of several studies in a single paper, 26 one study reported data in two separate publications, 3042 and data from another, unpublished study, was reported in a review article. 36 Two studies reported data from the Danish national pregnancy registry during overlapping time periods: one reported the risk of miscarriage among all births, 22 the other reported the risk of congenital anomalies among live births.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 For HIV-infected pregnant women, the use of prophylactic cotrimoxazole is associated with a reduction in preterm delivery and neonatal mortality in their HIV-exposed infants. 3 Since 2006, the World Health Organization (WHO) has recommended that cotrimoxazole prophylaxis should be provided to all HIV-infected individuals with a CD4 cell count <350 per mm 3 , particularly in resource-limited settings where bacterial infections and malaria are prevalent. 4 …”
Section: Introductionmentioning
confidence: 99%
“…At the individual level, nutritional and micronutrient support for women and infants may reduce infant mortality rates, as demonstrated by a recent study in Tanzania showing the benefit of maternal vitamin D replacement for infant survival [19]. Other interventions include prophylactic vaccinations, use of bed nets in areas where malaria is prevalent, and the provision of prophylactic sulfamethoxazoletrimethoprim to HIV-infected women in pregnancy and to infected infants [20,21].…”
Section: (See the Article By Kuhn Et Al On Pages 437-44)mentioning
confidence: 99%